Care associated with stillbirth for the most disadvantaged women: A multi‐method study of care in England. Issue 3 (13th February 2018) - Redshaw, Maggie; Henderson, Jane
Abstract: Background: Most research on women experiencing stillbirth relies on online user group surveys or qualitative interviews. The objective of this study was to investigate the experience of women who are at a higher risk of stillbirth, living in areas of greatest deprivation, and are commonly not well represented. Methods: This study used birth and death registrations in 2012‐2013 to identify a sample of mothers whose babies had died as a result of stillbirth. These women were sent a survey 6‐9 months after the stillbirth. We undertook descriptive analysis of quantitative data and used binary logistic regression with the Index of Multiple Deprivation as a measure of disadvantage. We used thematic analysis to describe free text responses. Results: The survey response rate was 30% (N = 473). Ethnic minority, younger age, and single parenthood were associated with disadvantage. Women residents in the most deprived areas perceived care more negatively: during labor they were significantly less likely to be spoken to by medical staff so they could understand (73% compared with 90%, adjusted odds ratio [aOR] 0.33 [95% confidence interval CI 0.18‐0.65]), or treated with respect by midwives (79% compared with 90%, aOR 0.41 [95% CI 0.22‐0.77]). The qualitative themes identified were: "Difficulty in accessing care, " "More could have been done, " "Ineffective communication, " and "Cared for and not cared for" which support the quantitative findings. Conclusion: Women living in the most deprived areas reported poorer experiences of care compared with more advantaged women. All women need compassionate and sensitive care around the time of a stillbirth.